How is income generated by outpatient parenteral antibiotic treatment (OPAT) in the UK? Analysis of payment tariffs for cellulitis. (3rd January 2015) - Jones, G. R.; Cumming, D. V. E.; Honeywell, G.; Ball, R.; Sanderson, F.; Seaton, R. A.; Healy, B.; Hedderwick, S.; Gilchrist, M.; ,; Dryden, Matthew; Gilchrist, Mark; et al.
Abstract: Objectives: We determined the available mechanisms to generate income from outpatient parenteral antimicrobial therapy (OPAT) in the UK and calculated the revenue generated from treatment of an episode of cellulitis. Methods: Revenue was calculated for patients receiving treatment for cellulitis as an inpatient and for patients receiving OPAT by a series of different payment pathways. Selected established OPAT services in Northern Ireland, Scotland and Wales, where Payment-by-Results (PbR) does not operate, were contacted to determine individual national funding arrangements. Results: In England, a traditional inpatient episode for uncomplicated cellulitis requiring 7 days of treatment generated £1361 of revenue, while OPAT generated revenue ranging from £773 to £2084 for the same length of treatment depending on the payment pathway used. Treatment using OPAT to avoid admission entirely generated £2084, inpatient admission followed by transfer to a virtual OPAT ward at day 2 generated £1361 and inpatient admission followed by discharge from hospital to OPAT at day 2 generated £773. In Northern Ireland, Scotland and Wales block contracts were used and no income was calculable for an individual episode of cellulitis. Conclusions: No single funding mechanism supports OPAT across the UK. In England, revenue generated by OPAT providers from treatment of cellulitis varied with the OPAT payment pathway used, but equalled or exceeded the income generated from equivalent inpatient care. Cost savings for OPAT and reuse of released inpatient beds will increase revenue further. A single OPAT tariff is proposed.